Therapeutic Efficacy of Crinum Asiaticum Leaf Extract Against Aeromonas Hydrophila Infection in Juvenile Common Carp (Cyprinus Carpio L.) - Azizah, Zahrina Hibatul (Aquatic Life Sciences, 2025)
Bacterial infections caused by Aeromonas hydrophila are a major problem in freshwater aquaculture, often leading to high mortality and economic losses. Plant-based alternatives are needed to reduce dependence on synthetic antibiotics and mitigate antimicrobial resistance. This study evaluated the therapeutic efficacy of Crinum asiaticum leaf extract against A. hydrophila infection in juvenile common carp (Cyprinus carpio; 7–9 cm, ±80 g). Fish were immersed in extract solutions at concentrations of 20 mL (P1), 40 mL (P2), and 60 mL (P3) per 36 L of water for a single 45-minute treatment. The experiment followed a Completely Randomized Design (CRD) with three treatments and three replicates. Clinical signs, feeding response, startle reflex, survival rate, and water quality were monitored for 14 days. More than half of the infected fish developed dropsy, exophthalmia, and hemorrhages within 72 hours. Fish treated with 20 mL extract recovered fastest, achieving complete lesion resolution and a 90% survival rate. In contrast, P2 and P3 showed prolonged symptoms and only 10% survival, likely due to physiological stress and mild toxicity caused by higher concentrations that may irritate gill tissues. Water quality remained within optimal ranges throughout the trial. The superior therapeutic performance of the 20 mL concentration is likely attributable to the synergistic action of alkaloids and flavonoids at moderate levels, which enhance antimicrobial activity without inducing stress. These findings indicate that 20 mL is the most effective and safest concentration for immersion therapy, reinforcing the potential of C. asiaticum as a natural treatment for sustainable freshwater aquaculture.